The most prominent aspects and components of sustainable development from the perspective of Islamic education - Alsulami, Ahlam Ateeq (Journal of Educational and Psychological Sciences, 2021)
The study aimed to build a cognitive perception of sustainable development and its characteristics, and mentioning the components of its most prominent aspects from the perspective of Islamic education, while citing Qur’anic verses and hadiths. The researcher also used the descriptive and deductive approach to reach objectives of the study. Several conclusions were reached in this study, including: The term of sustainable development did not come in the Holy Qur’an with such words , but rather it brought with the content and a deep understanding of the principle of succession and reconstruction of the earth, It has become clear that focusing on the material aspect of sustainable development and considering it the only force in the universe may lead to the spiritual and intellectual emptiness, and then the collapse of the civilizational and social structure of nations. Education is also the most important means of achieving sustainable development in society; as it provides it with its most important elements, namely children. Where sustainable devel-opment begins with the development of the human being himself, and the inculcation of lofty values and high morals; To reflect this on himself and his community, Islamic education has included the most prominent aspects of sustainable development, as it possesses the principles and rational methodological vision, While it made the methods and means when applied to the human being and the extent of his abilities and capabilities available to him, and that shows the extent of the flexibility of the Islamic educational system. The study deals with the concept of sustainable development and its relationship to Islamic education, while clarifying its characteristics and highlighting its aspects from an Islamic educational perspective. The study was prepared on four axes: The first axis is to clarify the concept and characteristics of sustainable development. The second axis: included a statement of the relationship of sustainable development with Islamic education. The third axis: The researcher presented the components of most prominent aspects of sustainable development (economic, environmental, and social) from the perspective of Islamic education.